WAVE-INFLUENCED DELTAS: GEOMORPHOLOGICAL IMPLICATIONS FOR FACIES RECONSTRUCTION - Bhattacharya Ja.P.; Giosan L. (My University, 2003)
A process-based facies model for asymmetric wave-influenced deltas predicts significant river-borne muds with potentially lower quality reservoir facies in prodelta and downdrift areas, and better quality sand in updrift areas. Many ancient barrier-lagoon systems and 'offshore bars' may be better reinterpreted as components of large-scale asymmetric wave-influenced deltaic systems. The proposed model is based on a re-evaluation of several modern examples. An asymmetry index A is defined as the ratio between the net longshore transport rate at the mouth (in m3 year-1 ) and river discharge (in 106 m3 month-1 ). Symmetry is favoured in deltas with an index below ≈ 200 (e.g. Tiber, lobes of the Godavari delta, Rosetta lobe of the Nile, Ebro), whereas deltas with a higher index are asymmetric (e.g. Danube - Sf. Gheorghe lobe, Brazos, Damietta lobe of the Nile). Periodic deflection of the river mouth for significant distances in the downdrift direction occurs in extreme cases of littoral drift dominance (e.g. Mahanadi), resulting in a series of randomly distributed, quasi-parallel series of sand spits and channel fills. Asymmetric deltas show variable proportions of river-, wave- and tide-dominated facies both among and within their lobes. Bayhead deltas, lagoons and barrier islands form naturally in prograding asymmetric deltas and are not necessarily associated with transgressive systems. This complexity underlines the necessity of interpreting ancient depositional systems in a larger palaeogeographic context.
Keywords: BARRIER ISLANDS; DELTAIC SEDIMENTATION; LITTORAL DRIFT; RESERVOIR PROPERTIES; SAND BODIES; TIDAL INLETS